FORMATION OF CIVIC ACTIVITY AMONG HIGH SCHOOL STUDENTS IN THE DIGITAL SPACE AS A WAY OF EDUCATION OF NATIONAL SOLIDARITY - Treitiak, Dmytro (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article reveals the peculiarities of using digital space in forming civic activity among high school students, as one of the fundamental values of national solidarity. The purpose of the study is to determine the ways of using digital tools to form civic activity among high school students. Achieving the set goal involves solving the following tasks: determining the formation of civic activity among high school students as an essential component of the education of national solidarity and characterizing the state of formation of civic activity among high school students; outlining the methods of using the digital space in the process of forming civic activity; determination of forms and methods of formation of civic activity among high school students using digital space. To achieve the goal and fulfill the tasks, the following methods were used: theoretical: analysis, synthesis, comparison, and systematization of materials related to forming civic activity among high school students; empirical: analysis of educational practice, surveys, and observations. While implementing the set tasks, the study analyzed and provided a list of priority areas of educational work in the digital space. The experience of foreign scientists who were engaged in the formation of civic activity of schoolchildren is characterized and provided for comparison. The article reveals the peculiarities of educational work with high school students. It provides some methods of working with the use of digital space and digital tools, which will be helpful in the formation of civic activity and take into account the age characteristics of high school students. Based on surveys, the existing level of civic activity of high school students, the potential of their involvement in various activities, and how the use of digital space can contribute to the growth of civic activity have been characterized. The study characterized and revealed the peculiarities of the influence of social networks on civic activity and formed the principles of their use to effectively promote the formation of an active civic position among high school students. The critical importance of the digital space in forming the civic activity of high school students is revealed, as the most convenient, popular and comfortable environment that will provide the opportunity to interact with young people most effectively and implement the necessary initiatives. The practical significance of this study is that its materials can be used by teachers of higher education institutions, vocational and technical educational institutions, researchers, postgraduate students, and students in the process of research and organizing educational work with young people.